Pengembangan Pemahaman Literasi Kitab Kuning Dengan Menggunakan Tekhnik Metode Halaqoh Pada Santri Pondok Pesantren Darunnajah Jakarta - rokimin; Much. Hasan Darojat (Universitas Darunnajah, Jakarta, Indonesia, 2024)
AbstractThe background of this research is the importance of improving the literacy of kitab kuning among students as an effort to maintain the Islamic scholarly tradition in Indonesia. Darunnajah Islamic Boarding School Jakarta, as one of the leading Islamic educational institutions, aims to enhance students' understanding of kitab kuning using the halaqah method technique. This technique was chosen because it is believed to create an interactive and conducive learning atmosphere for mastering kitab kuning material. This study employs a mixed methods approach, combining qualitative and quantitative approaches. The qualitative approach is used to understand the process of implementing the halaqah method technique, while the quantitative approach is used to measure the increase in students' understanding of kitab kuning literacy. Qualitative data were collected through observations and in-depth interviews with students and teachers, while quantitative data were obtained through written tests before and after the implementation of the halaqah method.The results of the study show that the implementation of the halaqah method technique significantly improves students' understanding of kitab kuning literacy. Students who participated in this method showed an increase in their written test scores, as well as their ability to read and understand kitab kuning texts. Additionally, the halaqah method also increased students' engagement and motivation in the learning process, creating a more dynamic and interactive learning environment. These findings imply that the halaqah method can be an effective alternative in teaching kitab kuning literacy in Islamic boarding schools.